The Monetary System of Holland - Greven, H. B. (Quarterly Journal of Economics, 1887)
[The following paper, by Professor H. B. Greven, of Leyden, was read before the economic section of the British Association at Manchester, September 7, 1887. It is to appear in connection with the forthcoming report, which Mr. Edward Atkinson has been commissioned to make for the State Department, on the present state of bimetallism in Europe; and it is to Mr. Atkinson's courtesy that the opportunity of presenting the report here is due. The paper will be found to be a valuable chapter in the monetary history of our time, and records an important example of the maintenance of silver at par with gold, by the familiar expedient of a limitation of quantity effected by the suspension of silver coinage.]